Maternal and Umbilical Cord Blood Lactate for Predicting Perinatal Death: a secondary analysis of data from a randomized controlled trial - Musaba, Milton W.; Nambozo, Brendah; Barageine, Justus K.; Ndeezi, Grace (BMC Pediatr, 2023)
In high resource settings, lactate and pH levels measured from fetal scalp and umbilical cord blood are widely used as predictors of perinatal mortality. However, the same is not true in low resource settings, where much of perinatal mortality occurs. The scalability of this practice has been hindered by difficulty in collecting fetal scalp and umbilical blood sample. Little is known about the use of alternatives such as maternal blood, which is easier and safer to obtain. Therefore, we aimed to compare maternal and umbilical cord blood lactate levels for predicting perinatal deaths. This was secondary analysis of data from a randomized controlled trial assessing the effect of sodium bicarbonate on maternal and perinatal outcomes among women with obstructed labour at Mbale regional referral hospital in Eastern Uganda. Lactate concentration in maternal capillary, myometrial, umbilical venous and arterial blood was measured at the bedside using a lactate Pro 2 device (Akray, Japan Shiga) upon diagnosis of obstructed Maternal lactate was a poor predictor of perinatal death, but umbilical artery lactate has a high predictive value. There is need for future studies on the utility of amniotic fluid in predicting intrapartum perinatal deaths. labour. We constructed Receiver Operating Characteristic curves to compare the predictive ability of maternal and umbilical cord lactate and the optimal cutoffs calculated basing on the maximal Youden and Liu indices. Perinatal mortality risk was: 102.2 deaths per 1,000 live births: 95% CI (78.1–130.6). The areas under the ROC curves were 0.86 for umbilical arterial lactate, 0.71 for umbilical venous lactate, and 0.65 for myometrial lactate, 0.59 for maternal lactate baseline, and 0.65 at1hr after administration of bicarbonate. The optimal cutoffs for predicting perinatal death were 15 0.85 mmol/L for umbilical arterial lactate, 10.15mmol/L for umbilical venous lactate, 8.75mmol/L for myometrial lactate, and 3.95mmol/L for maternal lactate at recruitment and 7.35mmol/L after 1 h.